Reuse of Single Use Medical Devices - Tapp, Ann (Operating Room Nurses Association of Canada Journal, 2003)
During the ten years that I have worked at the Canadian Nurses Protective Society, we have had numerous calls from Operating Room nurses questioning the practice of re—using single use medical devices in their facilities and voicing their concerns about possible harm to patients, themselves and potential liability exposure. Interest in this topic has been rekindled by the recent Saskatchewan case involving the death of a patient from variant Creutzfeld-Jakob Disease (VCJD) and possible transmission of vC]D to 71 patients who may have been exposed to the same endoscope as the deceased while in hospital. In this article, I propose to address some of the concerns related to the reuse of single use medical devices by focusing on the prevalence of this practice, the legal risks involved, regulation of this practice, and risk management.